Critical Path Method for Oil and Gas Projects - Badiru, Adedeji B.; Osisanya, Samuel O. (Project Management for the Oil and Gas Industry, 2013)
Like a pipeline network, activities that make up a project form a network of interrelationships. Consider the network in Figure 5.1. The complexity of the activity network in a large project increases rapidly with increase in the number of activities. Network analysis is essential for making sense out of the jumble of activities. Project scheduling is the time-phased sequencing of network activities subject to precedence relationships, time constraints, and resource limitations to accomplish specific objectives. The computational approaches to project network analysis using PERT, CPM, and PDM (precedence diagramming method) are presented. Several graphical variations of Gantt charts are presented. CPM network charts and Gantt charts are excellent visual communication tools for conveying project scope, requirements, and lines of responsibility.